Pemanfaatan Limbah Plastik Polyethylene Terephthalate (PET) dan Batok Kelapa Sebagai Bahan Baku Paving Block - Utama, Komang Muliandre; Warji, Warji; Rahmawati, Winda; Suharyatun, Siti (abe.fp.unila.ac.id, 2023)
In 2021 the total amount of waste from various types of waste in Indonesia alone will reach 68,5 milion tons. Based on these data, as much as 17 percent, or around 11,6 milion tons, was contributed by jenna R.Jambeck from the University of Geogia in 2010, there were 275 tons of plastic waste produced worlwide. Around 4,8-12,7 milion tons of them are waste and pollute the sea. Indonesia itself has a coastal population of 187,2 ,milion which annually produces plastic waste. Around 0,48-1,29 milion tonnes of plastic waste is thought to have polluted the oceans. To overcome this, proper management of plastic waste is needed, one of which is by making paving blocks made from plastic waste. The study aims to determine the characteristics of thr various composition paving blocks according to the Dquality standard, which is used for garden pavements and other uses. In this study, aratio of 1:1:1 was used for plastic, sand, and oil. Then coconut shells were added to the treatment P1 as much as 3%, P2 as much as 6%, P3 as much as 9%, and P4 as much as 12% of the paving block volume paving block quality standardD has requirements, namely the maximum value obtained from the results of the compressive strength test is 10 Mpa and water absorption is 10%. From the result of the research that i did, it was found that the variations in the P treatment were closestto the quality standard D, with a compressive strength test value of 5,84 Mpa. Keywords : Coconut Shells, Paving Blocks, PET, Plastic, Waste.